Language Analysis of Editorial Text in The Editorial Column of Radar Karawang Newspaper December 2023 Edition - Ummaya, Zaidiyah; Rosalina, Sinta; Setiawan, Hendra (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to describe the language of editorial texts contained in the editorial column of the December 2023 edition of the Radar Karawang newspaper . The results of the research are recommended as teaching material for editorial texts for class XII high school. This research uses a qualitative approach with descriptive methods. The research subject is the editorial column of the Radar Karawang newspaper, while the research object is the language of the editorial text. Data collection in this research used document techniques. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The results of this research found that the language of editorial texts includes rhetorical sentences; popular words; demonstrative pronouns that, this, that ; causality conjunctions because, because, therefore, blessing, effect; and the opposing conjunctions but, however, whereas, otherwise . The results of this research are recommended as handout teaching materials according to the 2013 Curriculum with Basic Competition 3.6 analyzing the structure and language of editorial texts for class XII high school. These teaching materials can be used as additional reference material for editorial texts for teachers and students.